The Evaluation of Federations' Administrative Issues from the Views of Executives - Alp Çelik (ümit doğan üstün, 2016)
The aim of this study was to receive the administrative opinions in order to evaluate the administrative issues of independent sport federations. For this purpose, qualitative research method has been used. Total of 47 independent sport federations were identified according to the number of active sportsman, number of medals, priority of branch upon society, being Olympic sport and being one of the fundamental sport branches. Face to face interviews have been made with administers in selected federations; 15 federation manager, 10 federation vice manager, 12 federation general secretary and 10 federation board members. Administers have supposed to reply the questions; "what are the administrative issues that federations face?", "what are the reasons of failure for sports branches from the administrative aspect?" Interview method has been used to collect the data and a semi-structured interview form was designed by the researcher. The interviews were recorded by a sound recorder and the descriptive analysis method was used for the analysis of data. According to the results, the financial situation has seemed to be the one of the most important issues of federations. It could be deduced that federations need financial support and there was a lack of self-revenues which administers face as a huge problem. Besides, it could be said that the federations should have been supported financially in order to remove the obstacles upon successes.